Situação vacinal infantil e características individuais e familiares do interior de São Paulo - Molina, Ana Cláudia; Godoy, Ilda de [UNESP]; De Carvalho, Lídia Raquel [UNESP]; Caldas Júnior, Antônio Luiz [UNESP] (My University, 2007)
The aim of this study was to describe and analyze individual and family characteristics of children and those of health services, as well as their relationship with the immunization status for different kinds of vaccines and doses. Three sources of information were used: records from the Municipal Health Information System, immunization charts, and interviews using closed-ended questions. The families interviewed still had one or two growing children; caretakers were usually young unemployed mothers with easy access to health services. Around 30% of them were not instructed on the vaccine being given, its reactions or when to return for the next shot. The greatest levels of tardiness occurred with the vaccines against measles (6.3%) and Haemophilus influenzae B (4.2%). It was possible to observe that tardiness or absence of vaccinations seem to have a stronger relationship with service characteristics than with population characteristics.
Childhood immunization status, and individual and family characteristics in the interior of São Paulo
Keywords: Health information system; Immunization; Missed opportunity for vaccination; Vaccination; Vaccination coverage; BCG vaccine; diphtheria pertussis tetanus vaccine; Haemophilus influenzae type b vaccine; caregiver; family; Haemophilus influenzae type b; health service; human; immunization; interview; measles; medical record; mother; vaccination; Haemophilus influenzae